PERANAN GURU DALAM PENGEMBANGAN KURIKULUM - Uranus Zamili (JURNAL PIONIR, 2020)
Curriculum development is implemented as an anticipatory step in responding to the challenges that arise as a result of these developments by taking into account the situation and conditions and norms that apply in society. The steps in curriculum development are arranged in such a way that they are essential so that students as components of learning get adequate competence in mastering and utilizing technology as desired. Science and technology always develop and progress according to the times and the development of human thinking. The advancement of science and technology has also led to developments in people's lives. These developments also cause changes in views of educational goals so that it is necessary to change and adjust the curriculum. Teachers have a very large attitude towards the success of learning in school. The teacher is very instrumental in helping the development of students to realize their life goals optimally. In this case, the teacher is required to be skilled in choosing or even combining approaches that are convincing to handle the right classroom management case with the problem at hand. Implementation of the curriculum requires someone who acts as the implementer. The teacher is an important factor in the implementation of the curriculum because it is implementing the curriculum. Therefore teachers are required to have the ability to implement it because without it the curriculum will not be meaningful as an educational tool. And conversely learning will not be effective without a curriculum as a guide. Key Word: Teacher Role, Curriculum, Development